Nephrotic Syndrome in Pediatric Patients - Frederick Jeffrey Kaskel (Frontiers Research Topics, 2017)
Nephrotic syndrome (NS) - characterized by heavy glomerular protein loss (proteinuria), edema, hypoalbuminemia, and hyperlipidemia - has diverse causes and frequently leads to chronic kidney disease. This E-book encompasses articles on a variety of topics in NS, including a historical perspective on understanding and treatment of NS, followed by state-of-the-art reviews of the molecular pathomechanisms, clinical outcomes, as well as current and emerging treatment strategies for NS. We hope that this comprehensive review will help to reduce the gaps between the research and the day-to-day care of patients with NS and inspire new research efforts towards updating and expanding the treatment armamentarium for the future.